First record of eudorylas schreiteri (Shannon) (Diptera: Pipunculidae) as a Parasitoid of the Corn Leafhopper (Hemiptera: Cicadellidae) in Argentina, with a table of pipunculid-host associations in the neotropical region - Virla, Eduardo Gabriel; Moya-Raygoza, Gustavo; Rafael, José Albertino (Neotropical Entomology, 2009)
The big-headed fly Eudorylas schreiteri (Shannon) is recorded for the first time as an endoparasitoid of the corn leafhopper Dalbulus maidis (DeLong & Wolcott) in Northern Argentina. A table of known Neotropical pipunculid-host associations is presented.
Keywords: Cicadellidae; Dalbulus Maidis; Diptera; Eudorylas; Hemiptera; Peregrinus Maidis; Pipunculidae